Zn-Zr / ZSM-5 / SrO photocatalyst and its preparation method and application
By uniformly doping Zn and Zr on ZSM-5 and compounding with SrO to form Zn-Zr/ZSM-5/SrO photocatalyst, the problem of limited response ability of the existing photocatalyst under visible light is solved, and efficient organic wastewater degradation effect is achieved.
Patent Information
- Application Number
- CN202510121175.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-26
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2045-01-26
AI Technical Summary
The existing photocatalysts have limited responsiveness under visible light, and the recombination rate of photogenerated electrons and vacancy is high, resulting in limited improvement in photocatalytic performance.
The Zn-Zr/ZSM-5/SrO photocatalyst is used to combine ethanol solution impregnation and high-temperature calcination to achieve effective recombination of Zn and Zr in ZSM-5 and SrO.
It significantly improves the separation efficiency between photogenerated electrons and vacancy, improves the redox capacity and structural stability, and shows excellent degradation performance. It degrades pollutants such as benzaldehyde and benzoic acid in organic wastewater at a fast rate and a high removal rate.
Smart Images

Figure CN119549186B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of photocatalysts and preparation thereof, and specifically relates to a Zn-Zr / ZSM-5 / SrO photocatalyst and a preparation method and application thereof. Background Art
[0002] As environmental pollution becomes increasingly serious, the treatment of organic wastewater has become an important issue that needs to be solved urgently. Although traditional wastewater treatment methods can remove pollutants in water to a certain extent, they often have disadvantages such as low treatment efficiency, high energy consumption, and easy secondary pollution. Therefore, it is particularly important to develop new wastewater treatment technologies that are efficient and environmentally friendly. Photocatalytic technology, as a green and sustainable wastewater treatment method, has attracted much attention because it can use solar energy to drive chemical reactions and degrade organic pollutants into harmless substances.
[0003] As a porous material with excellent catalytic performance, ZSM-5 molecular sieve has shown great application potential in the field of photocatalysis. However, the single ZSM-5 molecular sieve has limited response ability under visible light, and the recombination rate of photogenerated electrons and vacancies is high, which limits the improvement of its photocatalytic performance.
[0004] Zn and Zr are common doping elements with unique electronic structures and catalytic activities. However, they are usually unevenly distributed on the carrier, which greatly affects their performance and stability. If the barrier height is too high, it may hinder the transfer of photogenerated electrons; if the barrier is unstable, it may lead to an increase in the charge recombination rate, thereby reducing the photocatalytic efficiency. SrO is a wide bandgap semiconductor material. Due to its wide bandgap, SrO limits its light absorption range. SrO mainly absorbs ultraviolet light, while its absorption capacity for visible light is relatively weak. This means that under sunlight, SrO can only use a small part of the light energy for catalytic reaction, thus limiting the improvement of its photocatalytic efficiency.
[0005] In the January 2001 issue of the Chinese Journal of Catalysis, Yin Shuangfeng, Lin Jie and Yu Zhongwei published an article titled “Effect of Zinc Content on the Performance of Zn / HZSM-5 Catalysts”. The introduction of zinc component reduced the B acid on the surface of HZSM-5, increased the L acid, and increased the total acid content. The n-hexane conversion rate first decreased and then increased with the increase of zinc content, while the aromatics yield and aromatization selectivity first increased and then leveled off with the increase of zinc content. During the reaction, the carbon deposition rate, pore volume and specific surface area of the catalyst decreased faster with the increase of zinc content. The amount of Lewis acid on the catalyst surface was large, resulting in more side reactions and ultimately a lower yield of the target product. Summary of the invention
[0006] The technical problem to be solved by the present invention is to overcome the above-mentioned defects in the prior art and provide a Zn-Zr / ZSM-5 / SrO photocatalyst with strong redox ability, stable structure and excellent performance.
[0007] The present invention also provides a method for preparing a Zn-Zr / ZSM-5 / SrO photocatalyst, which is simple to operate, has low cost, and significantly improves the separation efficiency of photogenerated electrons and vacancies.
[0008] The present invention also provides the application of Zn-Zr / ZSM-5 / SrO photocatalyst to more efficiently degrade pollutants such as benzaldehyde and benzoic acid in organic wastewater, with fast degradation rate and high removal rate.
[0009] The preparation method of the Zn-Zr / ZSM-5 / SrO photocatalyst of the present invention comprises the following steps:
[0010] (1) Add Zn(NO3)2·6H2O and ZrO(NO3)2·2H2O to anhydrous ethanol, stir magnetically, add ZSM-5, continue stirring, heat and evaporate the ethanol to obtain a white solid;
[0011] (2) grinding the white solid to an average particle size of 50-100 μm and calcining to obtain Zn- and Zr-doped ZSM-5;
[0012] (3) Dissolve Zn and Zr doped ZSM-5 in anhydrous ethanol, stir magnetically, add Sr(NO3)2•2H2O, stir evenly, heat to evaporate the ethanol, and calcine the obtained solid to obtain Zn-Zr / ZSM-5 / SrO photocatalyst.
[0013] In step (1), Zn(NO3)2·6H2O and ZrO(NO3)2·2H2O are calculated as Zn and Zr, wherein the mass ratio of Zn to Zr is 1:3-2:1.
[0014] The mass ratio of Zn and Zr to ZSM-5 in step (1) is 1:8-1:55.
[0015] In step (1), the magnetic stirring time is 30 min-60 min, and the continued stirring time is 30 min-60 min.
[0016] The temperature for heating and evaporating ethanol in step (1) and step (3) is 50-60°C.
[0017] The calcination in step (2) is as follows: placing the product in a muffle furnace and heating it to 550-650° C. at a heating rate of 5-10° C. / min, and maintaining the calcination for 3-6 hours.
[0018] The calcination in step (3) is as follows: the obtained solid is placed in a muffle furnace and heated to 500-600° C. at a heating rate of 10-15° C. / min, and calcined for 3-6 hours.
[0019] The amount of Sr(NO3)2•2H2O added in step (3) is based on SrO, and the ratio of the sum of the mass of Zn and Zr to the sum of the mass of ZSM-5 and SrO is 0.01-0.05, preferably 0.01, 0.02, 0.03, 0.04 and 0.05.
[0020] A Zn-Zr / ZSM-5 / SrO photocatalyst is prepared by the preparation method of the Zn-Zr / ZSM-5 / SrO photocatalyst.
[0021] Application of the Zn-Zr / ZSM-5 / SrO photocatalyst: 10mg-30mg of the prepared Zn-Zr / ZSM-5 / SrO photocatalyst is added to an aqueous solution of benzaldehyde and benzoic acid (mixed at 20mg / L each) at a concentration of 20mg / L, stirred on a magnetic stirrer in the dark for 80-120min, and then started a condensation device under xenon lamp irradiation for degradation. Benzaldehyde and benzoic acid have similar molecular weights, so the volume of the solution hardly changes when mixed.
[0022] Specifically, the preparation method of the Zn-Zr / ZSM-5 / SrO photocatalyst comprises the following steps:
[0023] (1) Dissolve Zn(NO3)2·6H2O and ZrO(NO3)2·2H2O in anhydrous ethanol at a Zn / Zr mass ratio of 1:3-2:1, stir magnetically for 30 min-60 min, add ZSM-5, continue stirring for 30 min-60 min, heat to 50-60 °C to evaporate the ethanol, and obtain a white solid; the mass ratio of Zn and Zr to ZSM-5 is 1:8-1:55.
[0024] (2) Grind the white solid to an average particle size of 50-100 μm, put it into a semi-enclosed alumina crucible with a lid, place it in a muffle furnace and heat it to 550-650°C at a heating rate of 5-10°C / min, and keep calcining for 3-6 hours to obtain Zn and Zr doped ZSM-5.
[0025] (3) Dissolve Zn and Zr-doped ZSM-5 in anhydrous ethanol, stir magnetically for 30 min-60 min, add Sr(NO3)2•2H2O, stir evenly, heat to 50-60 °C to evaporate the ethanol, place the obtained solid in a muffle furnace and heat to 500-600 °C at a heating rate of 10-15 °C / min, calcine for 3-6 h to obtain Zn-Zr / ZSM-5 / SrO photocatalyst.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] (1) The preparation method of the Zn-Zr / ZSM-5 / SrO photocatalyst of the present invention adopts a strategy of combining ethanol solution impregnation with high-temperature calcination to achieve uniform doping of Zn and Zr in ZSM-5 and effective composite with SrO. The operation is simple and the cost is low. The prepared Zn-Zr / ZSM-5 / SrO catalyst has a stable structure and excellent performance, which provides a strong guarantee for the industrial application of the catalyst.
[0028] (2) The Zn-Zr / ZSM-5 / SrO photocatalyst prepared by the present invention exhibits excellent degradation performance under visible light irradiation, providing a new solution for the green treatment of organic wastewater. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a scanning electron microscope image of the Zn-Zr / ZSM-5 / SrO photocatalyst prepared in Example 1. DETAILED DESCRIPTION
[0030] The present invention will be further described below in conjunction with specific embodiments.
[0031] The raw materials and reagents used in the following examples and comparative examples are all commercially available products.
[0032] Example 1
[0033] The preparation method of the Zn-Zr / ZSM-5 / SrO photocatalyst comprises the following steps:
[0034] (1) Dissolve 4.6 mg Zn(NO3)2·6H2O and 2.6 mg ZrO(NO3)2·2H2O in 20 mL anhydrous ethanol and stir magnetically for 40 min. Add 24 mg ZSM-5 and continue stirring for 40 min. Heat to 55 °C to evaporate the ethanol to obtain a white solid.
[0035] (2) The white solid was ground to an average particle size of 80 μm, placed in a semi-closed alumina crucible with a lid, and placed in a muffle furnace and heated to 600 °C at a heating rate of 8 °C / min and calcined for 4 h to obtain Zn and Zr doped ZSM-5.
[0036] (3) Zn- and Zr-doped ZSM-5 was dissolved in 500 mL of anhydrous ethanol and stirred magnetically for 40 min. 420 mg of Sr(NO3)2•2H2O was added and stirred evenly. The mixture was heated to 55°C to evaporate the ethanol. The obtained solid was placed in a muffle furnace and heated to 550°C at a heating rate of 12°C / min and calcined for 4 h to obtain a Zn-Zr / ZSM-5 / SrO photocatalyst. The scanning electron microscope image is shown in FIG. Figure 1 As shown. Figure 1 It can be seen that ZnO, ZrO2 and SrO are all loaded on the ZSM-5 molecular sieve.
[0037] Example 2
[0038] The steps of this embodiment are the same as those of embodiment 1, except that 181 mg of Sr(NO3)2•2H2O is added in step (3) so that the ratio of the sum of the masses of Zn and Zr to the sum of the masses of ZSM-5 and SrO is 0.02, thereby obtaining a Zn-Zr / ZSM-5 / SrO photocatalyst.
[0039] Example 3
[0040] The steps of this embodiment are the same as those of embodiment 1, except that 102 mg of Sr(NO3)2•2H2O is added in step (3) so that the ratio of the sum of the masses of Zn and Zr to the sum of the masses of ZSM-5 and SrO is 0.03, thereby obtaining a Zn-Zr / ZSM-5 / SrO photocatalyst.
[0041] Example 4
[0042] The steps of this embodiment are the same as those of embodiment 1. In step (3), 62 mg Sr(NO3)2•2H2O is added so that the ratio of the sum of the masses of Zn and Zr to the sum of the masses of ZSM-5 and SrO is 0.04, thereby obtaining a Zn-Zr / ZSM-5 / SrO photocatalyst.
[0043] Example 5
[0044] The steps of this embodiment are the same as those of embodiment 1. In step (3), 38 mg Sr(NO3)2•2H2O is added so that the ratio of the sum of the masses of Zn and Zr to the sum of the masses of ZSM-5 and SrO is 0.05, thereby obtaining a Zn-Zr / ZSM-5 / SrO photocatalyst.
[0045] Example 6
[0046] The preparation method of the Zn-Zr / ZSM-5 / SrO photocatalyst comprises the following steps:
[0047] (1) Dissolve 4.6 mg Zn(NO3)2·6H2O and 7.8 mg ZrO(NO3)2·2H2O in 50 mL anhydrous ethanol and stir magnetically for 30 min. Add 200 mg ZSM-5 and continue stirring for 30 min. Heat to 60 °C to evaporate the ethanol to obtain a white solid.
[0048] (2) The white solid was ground to an average particle size of 50 μm, placed in a semi-closed alumina crucible with a lid, and heated to 550 °C in a muffle furnace at a heating rate of 5 °C / min and calcined for 6 h to obtain Zn and Zr doped ZSM-5.
[0049] (3) Dissolve Zn and Zr-doped ZSM-5 in 800 mL of anhydrous ethanol and stir magnetically for 30 min. Add 477 mg of Sr(NO3)2•2H2O and stir evenly. Heat to 50 °C to evaporate the ethanol. Place the obtained solid in a muffle furnace and heat to 550 °C at a heating rate of 10 °C / min. Calcinate for 6 h to obtain the Zn-Zr / ZSM-5 / SrO photocatalyst.
[0050] Example 7
[0051] The preparation method of the Zn-Zr / ZSM-5 / SrO photocatalyst comprises the following steps:
[0052] (1) Dissolve 4.6 mg Zn(NO3)2·6H2O and 1.5 mg ZrO(NO3)2·2H2O in 50 mL anhydrous ethanol and stir magnetically for 60 min. Add 13 mg ZSM-5 and continue stirring for 60 min. Heat to 50 °C to evaporate the ethanol to obtain a white solid.
[0053] (2) The white solid was ground to an average particle size of 100 μm, placed in a semi-enclosed alumina crucible with a lid, and placed in a muffle furnace and heated to 650 °C at a heating rate of 10 °C / min and calcined for 3 h to obtain Zn and Zr doped ZSM-5.
[0054] (3) Zn- and Zr-doped ZSM-5 was dissolved in 1.2 L of anhydrous ethanol and magnetically stirred for 60 min. 330 mg of Sr(NO3)2•2H2O was added and stirred evenly. The mixture was heated to 60 °C to evaporate the ethanol. The obtained solid was placed in a muffle furnace and heated to 600 °C at a heating rate of 15 °C / min. The solid was calcined for 3 h to obtain the Zn-Zr / ZSM-5 / SrO photocatalyst.
[0055] Comparative Example 1
[0056] This comparative example is the same as Example 1, except that the ZrO(NO3)2·2H2O in step (1) is removed to prepare a Zn / ZSM-5 / SrO photocatalyst.
[0057] Comparative Example 2
[0058] This comparative example is the same as Example 1, except that the Zn(NO3)2·6H2O in step (1) is removed to prepare a Zr / ZSM-5 / SrO photocatalyst.
[0059] Comparative Example 3
[0060] This comparative example is the same as Example 1, except that the Sr(NO3)2•2H2O in step (3) is removed to prepare a Zn-Zr / ZSM-5 photocatalyst.
[0061] Comparative Example 4
[0062] This comparative example is the same as Example 1, except that the ZSM-5 in step (1) is replaced by alumina to prepare a Zn-Zr / Al2O3 / SrO photocatalyst.
[0063] The performance parameters of the catalysts prepared in the above examples and comparative examples are shown in Table 1.
[0064] Table 1 Catalyst parameters
[0065]
[0066] The photocatalysts prepared in the above examples and comparative examples were applied as follows: 10 mg of the prepared photocatalyst was added to an aqueous solution of benzaldehyde and benzoic acid at a concentration of 20 mg / L, stirred in the dark on a magnetic stirrer for 100 min, and then irradiated with a xenon lamp at a power of 400 W, the condensation device was started, and the temperature was maintained at 0°C for degradation. The degradation results are shown in Table 2. The solubility of the mixed solution after 6 hours of reaction was detected by gas chromatography-mass spectrometry and the degradation rate was calculated. The contents of the benzaldehyde and benzoic acid were detected by liquid chromatography.
[0067] Table 2 Test results
[0068]
[0069] As can be seen from Table 2, in Comparative Example 1, no zirconium oxynitrate solution is added, and Zr is missing in the active ingredient. Since the doping of Zr ions introduces surface defects in the Zn-Zr / ZSM-5 / SrO photocatalyst, the lack of Zr will lead to a reduction in the number of active sites of the photocatalyst and a decrease in the light absorption capacity, thereby affecting the catalytic performance.
[0070] In Comparative Example 2, no zinc nitrate solution was added, and Zn was missing from the active ingredients. The doping of Zn ions also has an important influence on the performance of the photocatalyst, and it can work together with Zr ions to further regulate the structure and performance of the photocatalyst. The lack of Zn will reduce the lattice stability of the photocatalyst, and will also affect the formation of mesopores and the effective transfer of photogenerated carriers, thereby reducing the catalytic activity.
[0071] In Comparative Example 3, no strontium nitrate solution was added, and Sr was lacking in the active ingredients. Since Sr ions loaded on the surface of the Zn-Zr / ZSM-5 / SrO photocatalyst play multiple roles such as introducing surface defects, promoting mesopore formation and enhancing light absorption, the lack of Sr will lead to a decrease in the specific surface area of the photocatalyst, a decrease in the number of active sites, and a decrease in light absorption capacity, thereby affecting the catalytic performance.
[0072] In Comparative Example 4, ZSM-5 was replaced with alumina to prepare a Zn-Zr / Al2O3 / SrO photocatalyst. On the one hand, compared with ZSM-5, the particle size of Al2O3 is too large, which will reduce the specific surface area and the number of active sites; on the other hand, Al2O3 affects the recombination of photogenerated carriers, thereby affecting the photocatalytic degradation performance.
Claims
1. Application of a Zn-Zr / ZSM-5 / SrO photocatalyst in the degradation of benzaldehyde and benzoic acid in organic wastewater, characterized in that: The preparation method of the Zn-Zr / ZSM-5 / SrO photocatalyst comprises the following steps: (1) Add Zn(NO3)2·6H2O and ZrO(NO3)2·2H2O to anhydrous ethanol, stir magnetically, add ZSM-5, continue stirring, heat and evaporate the anhydrous ethanol to obtain a white solid; Zn(NO3)2·6H2O and ZrO(NO3)2·2H2O are calculated as Zn and Zr, wherein the mass ratio of Zn to Zr is 1:3-2:1; the mass ratio of the sum of Zn and Zr to ZSM-5 is 1:8-1:55; (2) grinding the white solid to an average particle size of 50-100 μm and calcining to obtain Zn- and Zr-doped ZSM-5; (3) Dissolve Zn and Zr-doped ZSM-5 in anhydrous ethanol, stir magnetically, add Sr(NO3)2•2H2O, stir evenly, heat to evaporate the anhydrous ethanol, and calcine the obtained solid to obtain a Zn-Zr / ZSM-5 / SrO photocatalyst; the amount of Sr(NO3)2•2H2O added is based on SrO, and the ratio of the sum of the mass of Zn and Zr to the sum of the mass of ZSM-5 and SrO is 0.01-0.
05.
2. The use of the Zn-Zr / ZSM-5 / SrO photocatalyst according to claim 1 in degrading benzaldehyde and benzoic acid in organic wastewater, characterized in that: In step (1), the magnetic stirring time is 30 min-60 min, and the continued stirring time is 30 min-60 min.
3. The use of the Zn-Zr / ZSM-5 / SrO photocatalyst according to claim 1 in degrading benzaldehyde and benzoic acid in organic wastewater, characterized in that: The temperature for heating and evaporating the anhydrous ethanol in step (1) and step (3) is 50-60°C.
4. The use of the Zn-Zr / ZSM-5 / SrO photocatalyst in degrading benzaldehyde and benzoic acid in organic wastewater according to claim 1, characterized in that: The calcination in step (2) is as follows: placing the mixture in a muffle furnace and heating it to 550-650° C. at a heating rate of 5-10° C. / min, and maintaining the calcination for 3-6 hours.
5. The use of the Zn-Zr / ZSM-5 / SrO photocatalyst in degrading benzaldehyde and benzoic acid in organic wastewater according to claim 1, characterized in that: The calcination in step (3) is as follows: the obtained solid is placed in a muffle furnace and heated to 500-600° C. at a heating rate of 10-15° C. / min, and calcined for 3-6 hours.
6. The use of the Zn-Zr / ZSM-5 / SrO photocatalyst in degrading benzaldehyde and benzoic acid in organic wastewater according to claim 1, characterized in that: 10 mg to 30 mg of the prepared Zn-Zr / ZSM-5 / SrO photocatalyst was added to an aqueous solution of benzaldehyde and benzoic acid at a concentration of 20 mg / L, stirred on a magnetic stirrer in the dark for 80 to 120 min, and then a condensation device was started under xenon lamp irradiation for degradation.